Parenting Self-Efficacy, Father Involvement, dan Stunting - Dyah Ayu Rahmawati; Abdul Haris Fitri Anto; Rahmawati Prihastuty; Yuni Sulistyawati (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This study aims to analyze the influence of parenting self-efficacy on father involvement in stunting prevention. The research is motivated by the high prevalence of stunting in Indonesia, despite recent declines. Further research is needed to explore the factors that contribute to reducing stunting, particularly the role of families in providing instrumental and emotional support. While co-parenting, where both fathers and mothers share responsibilities in raising and educating children, is ideal, the reality shows that father involvement in early childhood care remains very limited. This study employs a quantitative correlational method with a sample of 220 fathers in Semarang City, selected using convenience sampling. The study uses two measurement tools: the Self-Efficacy for Parenting Task Index (SEPTI) by Coleman & Karraker, adapted into Indonesian with 36 items. The results of a simple linear regression analysis indicate that parenting self-efficacy has a positive impact on father involvement in stunting prevention. Parenting self-efficacy plays a crucial role in stunting prevention and improving child health. The study also demonstrates that parenting self-efficacy increases father involvement in caregiving, although social and cultural differences may influence this relationship. A lack of father involvement not only increases the risk of stunting but also places a greater burden on mothers, which can negatively impact child well-being.